ANALYSIS OF FACTORS AFFECTING ECONOMIC GROWTH IN INDONESIA 2001-2021 - Wahyu Krisniawanti; Daryono Soebagiyo (SEAN Institute, 2023)
Economic Growth in a country is often related to policies that have been set by the government to overcome economic problems. This study aims to analyze the effect of Inflation, Rupiah Exchange Rate, Bi Rate, Exports and Imports on Economic Growth in 2001-2021. The type of research data is quantitative data with secondary data obtained from the Central Statistics Agency (BPS), Word Bank and Bank Indonesia (BI). In this study using multiple linear regression method with Ordinary Least Square (OLS) analysis tool. This study found that the Inflation variable has a positive and significant effect on Economic Growth. then the Exchange Rate variable has a negative and significant effect on Economic Growth. Bi Rate, Export and Import variables have no effect on Economic Growth. This needs control in policies regulated by the government for the purpose of increasing growth and the economy in Indonesia.